PEMIKIRAN AL-KINDI TENTANG PENDIDIKAN ISLAM DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Nova Mariyanti; Nunu Burhanuddin (CV. ADIBA AISHA AMIRA, 2023)
The aim is to examine Al-Kind's ideas related to Islamic education, his ideas and the implications of his ideas for contemporary Islamic education. In this study, the author uses qualitative research through a literature research approach, namely. Research conducted by collecting information and data from various library materials, such as reference books, previous similar research results, articles and various magazines. This study uses one major source of Al-Kindi: The Philosopher Of The Arabs by George N. Atiyeh and translated by Kasidjo Djojosuwarno. While secondary sources come from 20 books and 11 scientific publications related to Al- Kindi's thought. This research analyzes Al-kind's ideas about God, religion and philosophy, soul and mind, then analyzes these ideas to find their relevance in contemporary Islamic education. The results of this study show that the importance of Al-kindi thought in Islamic education today is seen in the design of Islamic curriculum or learning materials that are in accordance with Al-kindi divine thinking, 21st century learning, such as KMA No. 183 According to philosophical and religious thought, the purpose of Islamic education is in line with the thinking of the soul, and the qualification standards of graduates are in accordance with the thinking of the mind.